Cell-permeable organic fluorescent probes for live-cell long-term super-resolution imaging reveal lysosome-mitochondrion interactions - Yubing Han; Meihua Li; Fengwu Qiu; Meng Zhang; Yu-Hui Zhang (Nature Communications, 2017)
Studying interactions between lysosomes and mitochondria in living cells is difficult due to the limitations of existing probes. Here, the authors develop new cell-permeable fluorescent probes to image the dynamics of lysosomes and their physical interactions with mitochondria using super-resolution microscopy.